Desain dan Implementasi Website Sebagai Media Promosi Wisata Budaya di Kampung Adat Tarung Sumba Barat - Mardiana Tenal Bolo; Yulius Nahak Tetik; Maria Wilda Malo (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The development of digital technology affects tourism promotion strategies. Promotion of cultural tourism in remote areas. The Tarung Traditional Village (KA) is one of the trains located in West Sumba district that has cultural heritage and historical value but still cannot be promoted properly due to the lack of digital media. Therefore, the researcher created a website as a medium for promoting cultural tourism destinations for Tangung Train. The system development method applied is the waterfall model with phases of needs analysis, system design, implementation, and testing. Information collections are carried out through literature studies, observations with traditional and community managers, and direct interviews. The process of developing this system must be able to meet the community's information needs related to the profile of customary areas, customary houses, customary ceremonies, photo galleries and tour guides of the Tarong Train. The result of this research is to get promotional media for the Tarung Train in the form of an informative site about the potential of the Tarung Train containing train profiles, traditional houses, traditional ceremonies, photo galleries, and tourist guides. As well as promotion in the form of a website that is able to increase access to information from the general public and also introduce cultural image.